FLEXURAL BEHAVIOR OF RC BEAMS CONTAINS RUBBERIZED PIECES AND STRENGTHENED WITH CFRP SHEETS - Adnan Abdullah Adday; Ahmed Sultan Ali (Journal of Engineering and Sustainable Development, 2023)
When rubberized, concrete beams lose some of their flexural strength. Conversely, flexural strengthening accounts for a sizeable portion of the structural applications for external carbon fiber reinforced polymers (CFRP) sheets that strengthen reinforced concrete beams. In this study, externally bonded sheets of (CFRP) were used to compensate for the flexural strength loss brought on by using rubberized concrete in constructing the beams. The study's reinforced concrete beams were split into two groups, each with three beams. In the first group, waste tire rubber (WTR) replaced (5 and 10) % of the fine and coarse aggregate, respectively. The reference group is the second group of typical concrete-mixture beams without used tire rubber. Each beam measured (2.1 m ×0.3m × 0.2m) has the same tensile, compression, and shear reinforcement. Every group of concrete beams contained a beam without any external reinforcement, a beam with a single layer, and a beam with double layers of (CFRP) sheet, where the beam soffit was externally strengthened. ABAQUS' finite element analysis software was used to represent the third external strengthening layer numerically. The mechanical properties of the two groups have been tested; additionally, the flexural response of the beams was examined using a monotonic two-point loading. The outcomes denote that strengthening with one and two layers of (CFRP) sheet increases the first crack load (FCL) and failure load (FL) by (8.57 and 17.64) with (17.14 and 34.27) %, respectively. The first crack deflection (FCD) also increased by (58.64) and (78.19) %, while the failure deflection (FD) decreased by (13.25) and (5.42) %, respectively.